Improving interprofessional collaboration in pain clinics through simulation: a longitudinal Readiness for Interprofessional Learning Scale assessment - John Mekail; Ysaac Zegeye; Quinn Lanners; Muhammad Farooq Anwar; Peter K Yi (BMJ Open Quality)
Background Interprofessional collaboration (IPC) is vital for delivering safe, holistic patient care, particularly in outpatient interventional pain clinics where precision and teamwork are crucial. Despite its importance, IPC within outpatient pain medicine remains understudied, and the Readiness for Interprofessional Learning Scale (RIPLS) has not been used longitudinally in outpatient pain medicine.Objectives The primary objective of this quality improvement (QI) project was to evaluate and enhance readiness for interprofessional learning among clinical staff in an outpatient pain clinic, measured over 6 months in an outpatient pain clinic.Methods This initiative took place from October 2021 to April 2022 in an academic institution’s hospital-based outpatient pain clinic. We administered the RIPLS survey to 15 participants of various clinical roles at baseline and again 6 months after a simulation-based intervention. The simulation included small group didactic sessions and immersive clinical scenarios depicting acute complications in interventional pain procedures. We used descriptive statistics to compare preintervention and postintervention survey responses, stratifying by professional role. Qualitative feedback was collected to explore participants’ perceptions of the training and its impact.Results Both physician and non-physician groups reported high baseline RIPLS scores, with no statistically significant difference between or within groups over 6 months. Although mean RIPLS scores did not significantly change, participants consistently described positive attitudes towards collaborative practice. Qualitative feedback underscored the importance of structured simulation for reinforcing team roles, communication strategies and crisis management skills.Conclusion This project demonstrates that simulation-based training can sustain high levels of interprofessional readiness among outpatient pain clinic staff over time, suggesting utility for maintaining collaborative behaviours in a setting where safety and teamwork are paramount. Future efforts could investigate whether similar interventions improve IPC in clinics with lower baseline readiness, as well as explore longer follow-up periods or larger sample sizes to detect nuanced changes in collaboration metrics.